OPTIMALISASI PERAN STAKEHOLDER EKSTERNAL DALAM MENINGKATKAN KESEJAHTERAAN SDM DI ORGANISASI OLAHRAGA STUDI PADA KELIMUTU TAEKWONDO TEAM KOTA DEPOK - Hidayaturraihan, Hidayaturraihan; Ibrahim Bali Pamungkas (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Sports organizations play a role not only in fostering achievement but also in ensuring the well-being of the human resources involved. To improve human resource well-being, the role of external stakeholders is a crucial factor that needs to be optimized. External stakeholders, such as the government, sponsors, the community, and the private sector, play a strategic role in supporting the sustainability and development of sports organizations. This study aims to analyze and assess the optimization of the role of external stakeholders in improving human resource well-being in sports organizations, focusing on the Kelimutu Taekwondo Team. The main issue addressed in this study is the limited support from external stakeholders, which impacts the well-being of coaches, athletes, and organizational administrators. This research employed a qualitative approach with a case study method. Data collection techniques included interviews, observation, and documentation. The results are expected to provide an overview of the roles of external stakeholders, the obstacles encountered, and strategies for optimizing the role of external stakeholders in improving human resource well-being at the Kelimutu Taekwondo Team. This research is expected to provide evaluation material and recommendations for sports organizations in building sustainable collaborations with external stakeholders. Data collection techniques were conducted through interviews, participant observation, and documentation. The results indicate that external stakeholders play a significant role in providing financial, moral, and social support to coaches and administrators. However, optimizing this role is not yet fully structured and requires long-term communication strategies and collaboration. This study provides recommendations for strengthening institutional relationships between sports organizations and external stakeholders to create sustainable human resource welfare.